2021
DOI: 10.1002/ps.6315
|View full text |Cite
|
Sign up to set email alerts
|

Tracking pesticide exposure to operating workers for risk assessment in seed coating with tebuconazole and carbofuran

Abstract: BACKGROUND Coating seed with pesticides is an effective way to control plant pests, however, factory‐based coating processes may carry a potential risk to operational workers of chemical exposure. To study the risk, carbofuran and tebuconazole were used to coat corn seed and their subsequent distribution on the bodies of workers was measured at manufacturers XFS and LS (Shanxi, China). Clothing was collected from workers during operations and analyzed using high‐performance liquid chromatography. RESULTS At XF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…The analysis of the obtained results regarding the predominant localizations of the effect of pesticides on the workers' skin showed similarities with the results obtained in other experiments under other application conditions [11,12,13]. The primary exposure areas for all workers were the hands and lower limbs [11,12]. In the dermal and inhalation risk assessment, the risk index was much lower than 1 (mixing/loading: 0.000, application: 0.014), indicating that vineyard workers are at low risk of exposure to thiamethoxam [12].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The analysis of the obtained results regarding the predominant localizations of the effect of pesticides on the workers' skin showed similarities with the results obtained in other experiments under other application conditions [11,12,13]. The primary exposure areas for all workers were the hands and lower limbs [11,12]. In the dermal and inhalation risk assessment, the risk index was much lower than 1 (mixing/loading: 0.000, application: 0.014), indicating that vineyard workers are at low risk of exposure to thiamethoxam [12].…”
Section: Discussionsupporting
confidence: 82%
“…The analysis of the obtained results regarding the predominant localizations of the effect of pesticides on the workers' skin showed similarities with the results obtained in other experiments under other application conditions [11,12,13]. The primary exposure areas for all workers were the hands and lower limbs [11,12].…”
Section: Discussionsupporting
confidence: 81%
“…The lifetime carcinogenic and non-carcinogenic health risks associated with dermal exposure to the OCP-contaminated river water were considered nominal for the surrounding populations. Han et al [58] detected the dermal exposure and assessed the risk of pesticide exposure for those involved in the seed-coating process. The results of the study indicated that the levels of chemical exposure varied by the type of work undertaken and the region of a worker's body exposed.…”
Section: Routes Of Pesticide Exposurementioning
confidence: 99%
“…The routine-based planting of chemically treated seeds has raised several socio-economic, human health, and environmental concerns. This is because of the poor efficacy or inconsistent effectiveness of chemical seed treatments in controlling seed-and soil-borne pests (Rossman et al 2018;Mourtzinis et al 2019;Lundin et al 2020;You et al 2020;Fadel Sartori et al 2020); risk exposure to operators that treat seeds or handle treated seeds (White and Hoppin 2004;Han et al 2021); development of different forms of human cancer (AGRICAN 2020); and negative effects on non-target organisms such as bees (Rundlof et al 2015;Main et al 2020), birds (Li et al 2020b;Fernández-Vizcaíno et al 2021), and soil beneficial microorganisms (Nettles et al 2016;Zaller et al 2016;Gomes et al 2017). In addition, the planting of chemically treated seeds negatively affects beneficial plant fungal endophytes, involved in plant growth and development thereby reducing early plant growth (Vasanthakumari et al 2019).…”
Section: Introductionmentioning
confidence: 99%